2021
DOI: 10.1002/clen.202000288
|View full text |Cite
|
Sign up to set email alerts
|

Source and Risk Assessment of Trace Metals in Red Soils from Yunnan Province, Southwest China

Abstract: Trace metal pollution is one of the most concerning issues in Yunnan province, where red soil is the dominant soil. To investigate the sources of trace metals and assess their pollution level and potential risk, trace metal concentrations are measured in two red soil profiles from Yunnan province. Results show that Cr, As, and Zn are the most abundant trace metals in both profiles, and As and Cr might be pollutants because their concentrations are higher than the background values and the average concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…This paper uses Class III water quality in the Quality Standard for Groundwater (GB/T 14848-2017) as a benchmark. The calculation formula is as follows [26,27]:…”
Section: Assessment Of Pollution Factors 241 Improved Nemero Composit...mentioning
confidence: 99%
“…This paper uses Class III water quality in the Quality Standard for Groundwater (GB/T 14848-2017) as a benchmark. The calculation formula is as follows [26,27]:…”
Section: Assessment Of Pollution Factors 241 Improved Nemero Composit...mentioning
confidence: 99%
“…Common heavy metals include chromium, cadmium, arsenic, and lead [ 10 ]. A survey showed that the enrichment concentrations of As and Cr in Yunnan red soil were higher than the background value and average concentration of national standard soil [ 11 ]. Additionally, red soil pollution has concealment and hysteresis.…”
Section: Introductionmentioning
confidence: 99%